Językowe i kulturologiczne wyróżniki kresowych kulinariów utrwalone w wybranych regionalnych opracowaniach o Ziemi Lubuskiej = Linguistic and culturological characteristics of Polish Borderlands cuisine preserved in selected regional studies on Ziemia Lubuska region - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Cuisine is an integral element of any also Polish, culture. This article is a linguisticculturological reflection on Polish Borderlands` dishes and beverages (e.g. kutia ?wheat grain, poppy seeds and honey dish`, kumpiak "cured ham", mamałyga "maise fluor porridge", nadzianka "potato stuffed intestines", strudel, paska "Easter bread", "sosnówka" "pine liqueur") which are a part of regional "melting pot of flavors", and therefore the "culinary melting pot" of Ziemia Lubuska region.
Keywords: kulinaria; język; kultura; Kresy Wschodnie; Ziemia Lubuska; cuisine; language; culture; Polish Eastern Borderlands